2021
DOI: 10.1155/2021/7769581
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of the Effect of Low-Frequency Repeated Transcranial Magnetic Stimulation and Extracorporeal Shock Wave on Improving the Spasm of Flexor after Stroke

Abstract: Poststroke spasticity (PSS) patients with muscle spasticity are effectively relieved by low-frequency repetitive transcranial magnetic stimulation (rTMS) or extracorporeal shock wave treatment (ESWT). However, there are relatively few reports about the difference in the efficacy of rTMS and ESWT for PSS. In this study, we examined and recorded the levels of UE motor section of the Fugl–Meyer Motor Assessment Scale (FMA-UE), myoelectric signal time-domain range integral values (iEMG), Modified Ashworth Scale (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Through the final full-text review, 14 articles were ultimately included for this review. This study included eight research articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] on rTMS, one of which included three data sets, one article included two data sets and the other articles each had one data set. A total of 128 patients received rTMS in all studies, and 104 patients served as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Through the final full-text review, 14 articles were ultimately included for this review. This study included eight research articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] on rTMS, one of which included three data sets, one article included two data sets and the other articles each had one data set. A total of 128 patients received rTMS in all studies, and 104 patients served as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the treatment of ST patients with NMES is significantly effective, and its short-term effect is superior to local injection of type A botulinum toxin[ 44 ]. Although research on NMES treatment for ST is currently limited, it has achieved significant efficacy in treating post-stroke spasm and spastic cerebral palsy[ 45 - 48 ], providing more options for clinical spasm treatment.…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…For a long time, upper limb spasticity has been the difficulty in rehabilitation treatment for the dysfunction of patients with subacute and chronic stroke ( Gittler and Davis, 2018 ). The common methods for reducing patients’ muscle spasticity include rehabilitation therapy, electrical stimulation, drug therapy, botulinum toxin A, and surgery ( Hu et al, 2021 ; Xu D. et al, 2021 ; Hsu et al, 2022 ). However, these therapies have limitations to different degrees, and a single treatment regimen does not achieve satisfactory effects.…”
Section: Introductionmentioning
confidence: 99%